Lipocalin-2 Deficiency Attenuates Neuroinflammation and Brain Injury after Transient Middle Cerebral Artery Occlusion in Mice. Issue 8 (August 2014) - Jin, Myungwon; Kim, Jong-Heon; Jang, Eunha; Lee, Young Mi; Han, Hyung Soo; Woo, Dong Kyun; Park, Dong Ho; Kook, Hyun; Suk, Kyoungho
Lipocalin-2 (LCN2) is a secreted protein of the lipocalin family, but little is known about the expression or the role of LCN2 in the central nervous system. Here, we investigated the role of LCN2 in ischemic stroke using a rodent model of transient cerebral ischemia. Lipocalin-2 expression was highly induced in the ischemic brain and peaked at 24 hours after reperfusion. After transient middle cerebral artery occlusion, LCN2 was predominantly expressed in astrocytes and endothelial cells, whereas its receptor (24p3R) was mainly detected in neurons, astrocytes, and endothelial cells. Brain infarct volumes, neurologic scores, blood–brain barrier (BBB) permeabilities, glial activation, and inflammatory mediator expression were significantly lower in LCN2-defkient mice than in wild-type animals. Lipocalin-2 deficiency also attenuated glial neurotoxicity in astrocyte/neuron cocultures after oxygen-glucose deprivation. Our results indicate LCN2 has a critical role in brain injury after ischemia/reperfusion, and that LCN2 may contribute to neuronal cell death in the ischemic brain by promoting neurotoxic glial activation, neuroinflammation, and BBB disruption.